Enhancement of the physical adsorption of some insoluble lead compounds from drinking water onto polylactic acid and graphene oxide using molybdenum disulfide nanoparticles: Theoretical investigation - Mahdhi, Noureddine; Alsaiari, Norah Salem; Amari, Abdelfattah; Osman, Haitham; Hammami, Saber (Frontiers in Physics, 2023)
This study reports the enhancement of the physical adsorption of some insoluble lead compounds, from drinking water, onto polylactic acid (PLA) polymer and graphene oxide (GO) by filling with molybdenum disulfide (MoS2) nanoparticles (NPs). Based on the Lifshitz theory, we demonstrate the attractive nature of the van der Waals (vdW) interactions that are responsible for the physical adsorption between the cerussite (PbCO3), the pyromorphite (Pb5(PO4)3Cl), and the lead dioxide (PbO2) insoluble adsorbates and the GO/MoS2 and PLA/MoS2 adsorbent nanocomposites in water medium. Subsequently, we show an increase in the physical adsorption, at close and large separation distances (<100 nm) in the water medium, between the lead-insoluble adsorbate and the adsorbent GO/MoS2 and PLA/MoS2 nanocomposites by increasing the filling ratios (0%, 10%, 20%, and 30%) of MoS2 NPs. Moreover, for each lead-insoluble adsorbate, we demonstrate that the vdW adsorption potential and force were more important for GO/MoS2 than for PLA/MoS2 adsorbent. However, for a fixed filling rate, the physical adsorption was more important in the order PbO2 > Pb5(PO4)3Cl > PbCO3. Interestingly, we demonstrate that the physical adsorption strongly depended on the GO/MoS2 and PLA/MoS2 adsorbent type and weakly dependent to the lead compound adsorbates. For all “PbO2, Pb5(PO4)3Cl, and PbCO3” adsorbates, we demonstrate that the vdW adsorption potential and force were higher ∼6, ∼3.1, ∼2.2, and ∼1.9 times for GO than for PLA adsorbent for, respectively, filling ratios 0%, 10%, 20%, and 30% of MoS2 NPs.